The First Initial Boundary Value Problem for Parabolic Hessian Equations on Riemannian Manifolds (Communications in Mathematical Research, 2021)
For a class of elliptic Hessian operators, one type of correspondingparabolic Hessian equations is studied on Riemannian manifolds. The existence anduniqueness of the admissible solution to the first initial boundary value problem forthe equations are shown.